Empowerment and associative process of rural women: a case study of rural areas in Bogotá and Cundinamarca, Colombia - Suárez, Eliana; Mosquera, Teresa; Del Castillo, Sara (Agronomía Colombiana, 2018)
There are no formal female food production organizations in the municipalities of Sibate, Sopo or Sumapaz (Bogotá rural area). Additionally, in the organizations in which women participate, they usually do not hold a decision-making position, which inhibits economic and social development despite the fact that women play an important role in the entire food system (production, preparation, consumption and food utilization). The aim of this research was to characterize the empowerment of rural women as a consequence of associative processes that contribute to food and nutrition security using the "descriptive case" qualitative research methodology. The main results indicated that, even though the participation of women in associative processes promotes decision-making, access to agricultural inputs, technical assistance and economic autonomy, there are still inequalities and inequities between men and women. For these reasons, it is necessary to strengthen associative processes with a cross-cutting gender approach and provide space for participation where both women and men analyze and question traditional roles in the household in order to transform inequity gaps and, therefore, contribute to food and nutrition security.